Assessment of Rab geranylgeranyltransferase subunit beta in amyotrophic lateral sclerosis - Yang, Jing; Tian, Mei; Zhang, Lei; Xin, Cheng; Huo, Jia; Liu, Qi; Dong, Hui; Li, Rui; Liu, Yaling (Frontiers in Neurology, 2024)
Introduction Geranylgeranyltransferase Subunit Beta (RABGGTB) was expressed at higher levels in patients with Amyotrophic lateral sclerosis (ALS) compared with healthy controls. This study aims to observe the expression of RABGGTB in different cells from patients with ALS and different diseases. Methods In this case–control study, we collected peripheral blood from patients with ALS and healthy controls, and compared the expression of RABGGTB in natural killer cells (NK), T cells and B cells between patients with ALS and healthy controls by flow cytometry. And compared the expression of RABGGTB in monocytes and monocyte-derived macrophages from patients with ALS, Parkinson’s disease (PD), acute cerebrovascular disease (ACVD), and healthy controls by flow cytometry and immunofluorescence. Then flow cytometry was used to detect the expression of RABGGTB in monocytes from SOD1G93A mice and WT mice. Results The expression of RABGGTB was not significantly changed in NK cells, cytotoxic T cells (CTL), helper T cells (Th), regulatory T cells (Treg), and B cells from patients with ALS compared to healthy controls. And the expression of RABGGTB in monocytes and monocyte-derived macrophages was higher in the ALS group than in the PD, ACVD and control group. The expression of RABGGTB was significantly higher in monocytes of SOD1G93A mice compared to WT mice. Conclusion These findings suggest that RABGGTB expression was increased in monocytes and monocyte-derived macrophages from patients with ALS, not in NK, CTL, Th, Treg, and B cells. Future studies are needed to find the clinical implication of RABGGTB in ALS.